A set of empirical equations describing the observed colours of metal–anodic aluminium oxide–Al nanostructures - Cristina V. Manzano; Jakob J. Schwiedrzik; Gerhard Bürki; Laszlo Pethö; Johann Michler; Laetitia Philippe (Beilstein Journal of Nanotechnology, 2020)
Structural colours have received a lot of attention regarding the reproduction of the vivid colours found in nature. In this study, metal–anodic aluminium oxide (AAO)–Al nanostructures were deposited using a two-step anodization and sputtering process to produce self-ordered anodic aluminium oxide films and a metal layer (8 nm Cr and 25, 17.5 and 10 nm of Au), respectively. AAO films of different thickness were anodized and the Yxy values (Y is the luminance value, and x and y are the chromaticity values) were obtained via reflectance measurements. An empirical model based on the thickness and porosity of the nanostructures was determined, which describes a gamut of colours. The proposed mathematical model can be applied in different fields, such as wavelength absorbers, RGB (red, green, blue) display devices, as well as chemical or optical sensors.